Persistence of Maternal Anti-Rotavirus Immunoglobulin G in the Post–Rotavirus Vaccine Era. (19th November 2020) - Payne, Daniel C; McNeal, Monica; Staat, Mary Allen; Piasecki, Alexandra M; Cline, Allison; DeFranco, Emily; Goveia, Michelle G; Parashar, Umesh D; Burke, Rachel M; Morrow, Ardythe L
Abstract: To assess whether titers of anti-rotavirus immunoglobulin G persist during the post–rotavirus vaccine era, the Pediatric Respiratory and Enteric Virus Acquisition and Immunogenesis Longitudinal (PREVAIL) Cohort analyzed serum samples collected from Cincinnati-area mothers and young infants in 2017–2018. Rotavirus-specific antibodies continue to be transferred from US mothers to their offspring in the post–rotavirus vaccine era, despite dramatic decreases in childhood rotavirus gastroenteritis. Abstract : The PREVAIL Cohort of US mothers and their offspring found that US infants may continue to be protected against rotavirus gastroenteritis by maternally transferred, naturally acquired passive immunity, more than a decade after implementation of the US rotavirus vaccination program.